1996
DOI: 10.1111/j.1399-3054.1996.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate metabolism in one‐ and two‐year‐old spruce needles, and stem carbohydrates from three months before until three months after bud break

Abstract: Starch and sucrose metabolism of one‐ and two‐year‐old needles of Norway spruce (Picea abies [L.] Karst., about 30 years old) was investigated from three months before until three months after bud break at a natural site. We distinguish different metabolic states according to the extractable activities of enzymes (α‐amylase [EC 3.2.1.1], ADP‐glucose pyrophosphorylase [AGP, EC 2.7.7.27], D‐enzyme [EC 2.4.1.25], starch phosphorylase [STP. EC 2.4.1.1]), sucrose phosphate synthase [SPS, EC 2.4.1.14], sucrose syntb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 39 publications
5
22
1
Order By: Relevance
“…Similar to what found here (see also Hoch et al 2002), Fischer and Höll (1991) and Egger et al (1996) have documented a pronounced increase in starch immediately prior and during the time of bud break in mature needles. Since spring phenology lags from low to high elevations, our spring data collected before bud swelling/break possibly reflect a short term reversal of elevational trends, with trees at lower sites already accumulating starch, while those at treeline were still dormant (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to what found here (see also Hoch et al 2002), Fischer and Höll (1991) and Egger et al (1996) have documented a pronounced increase in starch immediately prior and during the time of bud break in mature needles. Since spring phenology lags from low to high elevations, our spring data collected before bud swelling/break possibly reflect a short term reversal of elevational trends, with trees at lower sites already accumulating starch, while those at treeline were still dormant (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Chlorophyll content, CO 2 assimilation (Zabuga and Zabuga 1981;Langenfeld-Heyser 1989), and photosynthetic refixation of CO 2 (Cernusak and Marshall 2000) as well as functional chloroplasts (Buns et al 1993) and carbohydrate metabolism (Egger et al 1996) have been reported earlier in stems and bark tissues of several evergreen conifers. In spite of these studies, no reliable information is available for the composition of the photosynthetic apparatus of the bark chlorenchyma in evergreen conifers and especially in Scots pine.…”
Section: Discussionmentioning
confidence: 96%
“…The accumulated assimilate pools in the stem and mostly in the bark are mobilized and support carbon supply to the new tissues after the bud break, when growth of shoots by cambial activity has started (Egger et al 1996). Although recovery of photosynthetic activity in evergreen conifers after the winter depression is a very early and fast event, occurring well before any cambial activity and visible growth (Ö quist and Huner 2003), our results suggest that the well preserved photosynthetic activity of the cortical stem chloroplasts may have a significant impact on the recovery of the photosynthetic apparatus in pre-existing overwintering needles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carlyle 1995). In winter and spring, a proportion of new wood is formed via remobilisation of C fixed during autumn (Egger et al 1996). Hence the δ 13 C signal of winter and spring wood represents a variable amount of retranslocated C as well as some from current photosynthesis.…”
mentioning
confidence: 99%